Strategies To Improve Performance - Pohan, Sarinah; Robain, Wilchan; Rahayu, Sri (PT. Multidisciplinary Press Indonesia, 2024)
This research was carried out to see the influence of Work Ethic and Work Discipline on Employee Performance with Competence as an Intervening Variable in the State Civil Service in Medan Baru District. This research used a path analysis model with the smart PLS version 3.3.3 measurement method. Data collection was carried out by giving questionnaires to respondents. This type of research uses quantitative research and primary data sources as the data source. The results of this research are as follows: Work Discipline has a positive and significant effect on Employee Performance with an original sample value of 0.427 and a p value of 0.006. Work Discipline has a positive and significant effect on Competency with an original sample value of 0.756 and a p value of 0.000. Work Ethic has a positive and significant effect on employee performance with an original sample value of 0.267 and a p value of 0.006. Work Ethic has a positive and significant effect on Competency with an original sample value of 0.234 and a p value of 0.000. Competency has a positive and insignificant effect on employee performance with an original sample value of 0.277 and a p value of 0.059. Work Discipline has a positive and insignificant effect on Employee Performance indirectly through Competency with an original sample value of 0.209 and a p value of 0.059. Work Ethic has a positive and insignificant effect on employee performance indirectly through Competency with an original sample value of 0.065 and a p value of 0.091.